6(y-3)+3y-7=

Simple and best practice solution for 6(y-3)+3y-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y-3)+3y-7= equation:


Simplifying
6(y + -3) + 3y + -7 = 0

Reorder the terms:
6(-3 + y) + 3y + -7 = 0
(-3 * 6 + y * 6) + 3y + -7 = 0
(-18 + 6y) + 3y + -7 = 0

Reorder the terms:
-18 + -7 + 6y + 3y = 0

Combine like terms: -18 + -7 = -25
-25 + 6y + 3y = 0

Combine like terms: 6y + 3y = 9y
-25 + 9y = 0

Solving
-25 + 9y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + 9y = 0 + 25

Combine like terms: -25 + 25 = 0
0 + 9y = 0 + 25
9y = 0 + 25

Combine like terms: 0 + 25 = 25
9y = 25

Divide each side by '9'.
y = 2.777777778

Simplifying
y = 2.777777778

See similar equations:

| 3x-8y=-20 | | 5x-5=4x+8 | | 24x+3(-4+2x)=42 | | y=12.5(14)+150 | | 0.03(3x-36)=-0.9(x-1) | | 4x+14=17x-12 | | 5x^(-1/3)=20 | | 225=.04s | | -1/2p-3=3 | | 20x+y+12=180 | | 9-1=2h | | 36=r(18.5+r) | | x(500+3)=0 | | -1-7u=-15-8u | | X^3-2x^2-10x=0 | | 19j-16j+1=19 | | 9x+3=7x-1 | | 77x-1=67x-1 | | 9x-8x+5=17 | | 12+8x=x+47 | | -13x+23y=-7 | | 70=x+3+x+3+3x-8+3x-8 | | 4(b+1)=20 | | 7a-6a-1=15 | | 2(t-8)=4 | | (2y+x)dx+ydx=0 | | -5-5r=7-17r | | x+112=2x+68 | | 8-3(2x-3)=-4 | | x^2+4x+7=6 | | y-2=x/3 | | 14-4(3x-5)=-6 |

Equations solver categories